Rıb-Derived Lesion Mımicking Primary Pulmonary Ewing Syndrome - Akarsu, Saadet; Yildirim, Nezahat Bal; Poyraz, Ahmet Kursat (Edurad, 2024)
Only sporadic cases of primary pulmonary Ewing sarcoma (PES) have been reported in the scientific literature. Only 4 of the 50 reported cases are in the pediatric age group. It should be monitored that these cases are truly PES. Advanced imaging should investigate whether the actual origin is another structure. Our case, which appeared to be PES, but was understood to have rib origin after advanced imaging (positron emission tomography-PET/CT) and the first course of chemotherapy. Our case was thought to be PES based on initial clinical imaging. However, after advanced imaging (positron emission tomography-PET/CT) and the first chemotherapy course, it was understood that it originated from the ribs. The diagnosis of PES is very rare and it is important for those diagnosed to be followed closely for the correct origin. We wanted to report this to emphasize the effect of appropriate imaging and follow-up on treatment success. We wanted to emphasize the impact of appropriate imaging and actual diagnosis on the type of treatment and its success.
Keywords: Ewing Sarcoma; Extra-Skeletal Ewing Sarcoma; Thoracopulmonary Ewing Sarcoma; Primary Pulmonary Ewing Sarcoma